2012
DOI: 10.7439/ijbar.v3i4.426
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Intravenous Iron Sucrose Versus Oral Iron Therapy in Iron Deficiency Anemia During Postpartum Period

Abstract: Background:-Nutritional anemia is one of major contributory factor in high maternal mortality and morbidity in third world countries. Iron deficiency is the principle cause for nutritional anemia. The aim of the study was to compare the efficacy of oral iron therapy with intravenous iron therapy in the treatment of iron deficiency anemia during postpartum period Material and Methods:-A clinical observational study was undertaken at tertiary care teaching hospital over a period of 15 months in one hundred recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…Similar observations were reported in other studies like Prashant S. Kharde et al, Bayoumeu F et al and Khurshid Shabbir Raja et al without serious adverse effects. 15,17,18 This study is comparable with other two studies. In a study done by Agarwal Rohina S et al in 2010, showed baseline Hb 6.2g% and 5.95g%, Haematocrit 18.8 and 17.8%, MCV 71.28 and 70.1fl in IV and oral group respectively.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Similar observations were reported in other studies like Prashant S. Kharde et al, Bayoumeu F et al and Khurshid Shabbir Raja et al without serious adverse effects. 15,17,18 This study is comparable with other two studies. In a study done by Agarwal Rohina S et al in 2010, showed baseline Hb 6.2g% and 5.95g%, Haematocrit 18.8 and 17.8%, MCV 71.28 and 70.1fl in IV and oral group respectively.…”
supporting
confidence: 80%
“…The average rise of haemoglobin was 3.54g/dl and 5.3g/dl in oral and IV group respectively. 15 In another study done by Momen. AI et al in 1996, has shown baseline Hb 7.58 and 7.66g% and MCV 68.6 and 70.8fl/cell in IV and oral group respectively.…”
mentioning
confidence: 99%
“…They noted a faster increase in hematocrit value in the intravenous group from first to fourth postpartum week with 80% of the intravenous group and 40% of the oral group attaining their target hemoglobin of 12 g/dL. Similarly, Seid et al,35 Kharde et al36 and Van Wyck et al37 observed that the use of intravenous ferric carboxymaltose was associated with statistically significant rise in hemoglobin than in the oral group during treatment of postpartum anemia.…”
Section: Discussionmentioning
confidence: 88%
“…14 Similarly, in the study conducted by Kharde et al, the average rise of haemoglobin was 3.54 g/dl and 5.3 g/dl in oral and IV group respectively with no major side effects in any of the cases. 15 With all these studies, it is clearly evident that there is an effective rise in hemoglobin level with Intravenous iron Sucrose. The mean base line haematocrit (PCV) is 26% and post treatment mean PCV improved to 34% which is highly reassuring.…”
Section: Discussionmentioning
confidence: 98%